Virtual Social Networks as Contemporary Media Devices - Beltrán, Daniel Ernesto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this article is to inquire into the way in which virtual social networks are established as modulators of consumption and production of information, framed in the new dynamics of the globalized market. From an analytical and empirical perspective, a mixed nature approach to the content analysis was implemented, in order to study the multimodal resources found in the different interactive tools and mechanisms of the social networks. The main finding of this research is that the disposition of virtual social networks (VSN) towards the production and consumption of information is achieved thanks to the multimodal resources that form part of the interactive tools and mechanisms of the social networks. This fact illustrates the way in which VSN are established as new modulators of media control.